2019
DOI: 10.15441/ceem.18.081
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor prognosis in patients with heat stroke

Abstract: Objective The predictors of poor prognosis in heat stroke (HS) remain unknown. This study investigated the predictive factors of poor prognosis in patients with HS. Methods Data were obtained and analyzed from the health records of patients diagnosed with heat illness at Ajou university hospital between January 2008 and December 2017. Univariate and multivariate analyses were performed to identify the independent predictors of poor prognosis. Results Thirty-six patients (median age, 54.5 years; 33 men) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Elevated lactate levels are often seen in conditions with low perfusion, such as sepsis, shock, and trauma [25][26][27][28]. Studies have also shown elevated lactate levels in patients with HS [29][30][31], potentially due to factors like hypoxia, ischemia, and hyper-metabolism [29,32]. In this study, the nonsurvival group had signi cantly higher lactate levels compared to the survival group.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Elevated lactate levels are often seen in conditions with low perfusion, such as sepsis, shock, and trauma [25][26][27][28]. Studies have also shown elevated lactate levels in patients with HS [29][30][31], potentially due to factors like hypoxia, ischemia, and hyper-metabolism [29,32]. In this study, the nonsurvival group had signi cantly higher lactate levels compared to the survival group.…”
Section: Discussionmentioning
confidence: 59%
“…Elevated lactate levels are often seen in conditions with low perfusion, such as sepsis, shock, and trauma [25][26][27][28]. Studies have also shown elevated lactate levels in patients with HS [29][30][31],…”
Section: Discussionmentioning
confidence: 99%
“…The causes of death in heatstroke closely resemble the end-stage clinical features of sepsis, which are respiratory failure, acute respiratory distress syndrome, nosocomial pneumonia, renal failure, GI bleeding, stress gastritis, anemia, deep venous thrombosis, electrolyte abnormalities, hyperglycemia, hepatic dysfunction, and disseminated intravascular coagulation. [ 21 ] Consequently, bacterial translocation and endotoxemia from the GI system caused by systemic insults associated with heat stress lead to a systemic inflammatory response that mimics sepsis, and that can deteriorate rapidly to multiple organ failure and death. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this context, biomarkers that would aid in the early detection of injury and predict delayed brain damage would be crucial. Notably, S100 calcium‐binding protein β (S100β) (Chun et al., 2019; Li et al., 2020) and neuron‐specific enolase (NSE) (Li et al., 2020) have been recently proposed as potential biomarkers of heatstroke encephalopathy.…”
Section: Brainmentioning
confidence: 99%
“…However, additional work refutes these findings during exercise in the heat (Cheuvront et al., 2008) and passive heat stress (Shepley et al., 2021) models in humans. Nonetheless, two recent studies in heatstroke patients demonstrated elevated S100β protein in the serum and cerebrospinal fluid of heatstroke patients (Chun et al., 2019; Li et al., 2020), with one study finding that the heatstroke patients with poor prognosis (defined as not being able to live without assistance at hospital discharge) having serum S100β concentrations ∼5 times higher than in heatstroke patients with a good prognosis (Chun et al., 2019). NSE is a dimeric isoform of the glycolytic enzyme enolase expressed mainly in neurons (Kaiser et al., 1989).…”
Section: Brainmentioning
confidence: 99%